Queer philosophy : presentations of the Society for Lesbian and Gay Philosophy, 1998-2008 - Halwani, Raja.; Quinn, Carol Viola Anne.; Wible, Andy. (Value Inquiry Book Series, 2012)
The book is a collection of the presentations of the Society for Lesbian and Gay Philosophy from 1998 to 2008. The essays are organized historically, starting in 1998. Their topics cover virtually every philosophical field, and such that each is connected to gay and lesbian studies. Topics include how we are to understand sexual orientation, whether same-sex leads to polygamy, teaching gay studies to undergraduates, promiscuity and virtue, the "war on terror" and gay oppression, the rationality of coming out, the ethics of outing, connections between being gay and being happy, and last, but not least, dignity and being gay.